Shout - Bakker, Sabine Lubbe; Gould, Ester (PvH film, 2009)
Verzio FF Best friends Ezat and Bayan are about to make the journey they have planned since they were children. Born on the Israeli-occupied Golan Heights, they have lived all of their lives right next to the closed border with their homeland Syria. Now eighteen, they're given the opportunity to cross the UN-monitored no-man's land to study in Damascus. Feeling young, invincible and a hundred percent Syrian, they say goodbye to their village and families, knowing they won't be able to return for the next year. Like young people all over the world, Ezat and Bayan are pursuing their dreams and ambitions, and in Damascus they enjoy their new freedom. But the city also proves to be an anonymous place, where it's not easy to feel at home and where you have to watch what you say. What started as an adventure turns into a dilemma that forces them to choose between the future they always dreamt of and the secure environment they left behind.